2020
DOI: 10.1200/jco.19.03292
|View full text |Cite
|
Sign up to set email alerts
|

TBCRC 031: Randomized Phase II Study of Neoadjuvant Cisplatin Versus Doxorubicin-Cyclophosphamide in Germline BRCA Carriers With HER2-Negative Breast Cancer (the INFORM trial)

Abstract: PURPOSE Platinum compounds have activity in triple-negative breast cancer (TNBC) in germline BRCA mutation carriers ( BRCA carriers). Limited data exist for estrogen receptor (ER)–positive (+) breast cancer among BRCA carriers. INFORM is a randomized, multicenter, phase II trial comparing pathologic complete response (pCR) rates (ypT0/is, N0) after neoadjuvant single-agent cisplatin (CDDP) versus doxorubicin-cyclophosphamide (AC) in BRCA carriers with stage I-III human epidermal growth factor receptor 2 (HER2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 14 publications
2
85
0
2
Order By: Relevance
“…Several studies have shown that among ovarian cancer patients, BRCA1 and especially BRCA2 carriers respond better than non-carriers to platinum-based chemotherapy and have prolonged survival [20][21][22] . We hypothesized that BRCA germline mutations would lead to prolonged survival in breast cancer patients treated by DNA-damage agents such as alkylating agents and/or anthracylines 23 . We conducted a multicentric retrospective study with the primary objective of assessing the prognostic value of BRCA germline mutation on survival among stage I-III breast cancer patients treated with chemotherapy.…”
mentioning
confidence: 99%
“…Several studies have shown that among ovarian cancer patients, BRCA1 and especially BRCA2 carriers respond better than non-carriers to platinum-based chemotherapy and have prolonged survival [20][21][22] . We hypothesized that BRCA germline mutations would lead to prolonged survival in breast cancer patients treated by DNA-damage agents such as alkylating agents and/or anthracylines 23 . We conducted a multicentric retrospective study with the primary objective of assessing the prognostic value of BRCA germline mutation on survival among stage I-III breast cancer patients treated with chemotherapy.…”
mentioning
confidence: 99%
“…In addition to studies with carboplatin, cisplatin 75 mg/m 2 , every three weeks × 4 was evaluated in a randomized phase II study of neoadjuvant cisplatin vs. AC in germline BRCA carriers with HER2-negative (TBCRC 031) [46]. The pCR rate was 18% with cisplatin and 26% with AC, yielding a risk ratio (RR) of 0.70 (90% CI, 0.39 to 1.20).…”
Section: Platinum In Tnbcmentioning
confidence: 99%
“…All the studies included early breast cancer patients, two studies included Stage I-III patients (9,14), and the other three included Stage II-III patients (10,11,13). Three studies included only TNBC (10,13,14) and one study included HER2-patients (11). For study design, study by Hahnen et al, Loible et al, and Tung et al were randomized controlled trial (RCT) (10,11,13), and the other two were prospective cohort studies (PCS) (9,14).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies included only TNBC (10,13,14) and one study included HER2-patients (11). For study design, study by Hahnen et al, Loible et al, and Tung et al were randomized controlled trial (RCT) (10,11,13), and the other two were prospective cohort studies (PCS) (9,14). Two studies involved merely BRCA1 mutated patients (9,14), while the other three involved both BRCA1 or 2 mutated patients (10,11,13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation